Association between blood pressure and acute phase stroke case fatality rate: a prospective cohort study - Furlan, Natalia Eduarda [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; Braga, Gabriel Pereira [UNESP]; Novelli e Castro, Meire Cristina [UNESP]; Silva Franco, Roberto Jorge da [UNESP]; Gut, Ana Lucia [UNESP]; Bazan, Rodrigo [UNESP]; Martin, Luis Cuadrado [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2018)
Objective: ed to investigate the association between blood pressure and acute phase stroke lethality in a Brazilian intensive care unit. Methods: This was an observational, prospective cohort study of hemorrhagic and ischemic stroke intensive care patients. The primary outcome was all-cause mortality during the first seven days. Results: There were 146 patients, aged 66 +/- 13.4 years, 56% men, 89% Caucasian, 69% had ischemic stroke, and 80% were hypertensive. The median of the National Institutes of Health Stroke Scale score was 16. There were 101 ischemic stroke patients and 45 hemorrhagic stroke patients. In the ischemic stroke patients, logistic regression analysis identified low systolic blood pressure as an independent ominous prognostic factor and the optimal cut off was a mean of systolic blood pressure <= 131 mmHg during the first 48 hours from admission for prediction of death. No association was found for hemorrhagic stroke. Conclusions: There was a negative association between systolic blood pressure and case fatality ratio of acute phase stroke in ischemic stroke intensive care patients.
Keywords: stroke; blood pressure; hypertension